An analysis of the suitability of students' civic knowledge and disposition in the topic of citizen's rights and obligations - Dwi Riyanti (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2020)
Civic Education has been taught in primary education, but it has not impacted significantly with no strength and function. It is proven by the number of youths who have not understood and implement the citizen right and obligation (hak dan kewajiban warga negara) topic in Civic Education for their daily life. Thus, civic knowledge and civic disposition have not run as expected. This matter has become a great task for Civic Education lecturers to maximize and correlate comprehensively civic knowledge and civic disposition. This study discussed the suitability of civic knowledge and civic disposition in the topic of “Hak dan Kewajiban Warga Negara”. This study was descriptive research with a qualitative approach conducted in Universitas Negeri Yogyakarta (UNY), Universitas Ahmad Dahlan (UAD), SMKN 1 Kalikajar (Vocational High School), SMPN 1 Magelang (Junior High School), and SD Kembangsongo (Elementary School) and focused on Civic Education subject by using purposeful sampling. The data were collected through interviews and documentation. The data were then analyzed through the triangulation technique. This study resulted that students in their daily life have not fully implemented both civic knowledge and civic disposition. The matter was caused by students and lecturers of the Civic Education, whereas the subject’s topic has met the criteria of the curriculum in the level of Elementary School, Junior High School, and Senior High School/Vocational High School although not all topics were taught in these levels.